Mechanical baby pig feeder - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1970)
Various types of mechanical units designed to replace lactating brood sows are available. The Mini-Mor Corporation, Omaha, Nebraska, lent Kansas State University a unit designed to raise 36 pigs in individual cages. We are not trying to replace the lactating sow but to save baby pigs when they lose their mothers, or when a sow has more pigs than teats. The unit also could be used with large litters, for pigs that are pushed back and obviously are not getting enough to eat when a few days old.; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Baby pig feeder